MILITARY STRENGTH COMPARISON BETWEEN INDONESIA AND THAILAND IN MAINTAINING NATIONAL SECURITY - Bryan Nathanael; Hendra Maujana Saragih; Nabila Nur Afifah; Andi Dwi Cahya Karuniawan; Kartika Lefinski Deda (Journal of Social Political Sciences, 2023)
It is no question that national security is an important aspect of any country’s existence in the world. It is important that a country has a vital foundation to increase the nation’s progress, resilience against problems and an effective preparedness against any situation that may arise in the future. The focus of discussion in this paper is to compare the military strength of Indonesia and Thailand as both countries in Southeast Asia and ASEAN and a comparison of their national security objectives. This paper uses qualitative research methods to research the equipment, strength, soft and hard factors that impact the strength of Thailand and Indonesia’s military strength and National security policies which will be analyzed descriptively and explanatively. It is no question that Thailand and Indonesia have differing national strategies considering that the geographical characteristic of each country is quite vastly different with differing economical capabilities, internal challenges, military equipment. Both countries try to match their national strategies with their military’s capabilities. Where their differences in national security policy end in between the two countries is the continued cooperation between the two countries in the Association of Southeast Asian Nations (ASEAN) countries using integrated Military and Non-Military components (economy, culture, identity) in order to safeguard, protect and maintain their and other countries in ASEAN’s national interests.